The impact of sustainable finance development on energy efficiency in emerging economies - Liu, Xing; Lan, Minghui; Wang, Xiaonan; Zhang, Yongji; Su, Zhi (Frontiers in Environmental Science, 2023)
One of the best ways for nations to achieve sustainable economic development in the modern era is by accelerating energy transformation and enhancing energy efficiency. Sustainable finance plays a crucial role in bridging economic development and environmental protection. This study gathered data from 259 Chinese cities between 2010 and 2019 and used it to assess how sustainable finance affects the growth of energy efficiency. The empirical findings demonstrate that sustainable finance supports advancing energy efficiency through technological innovation and optimizing industrial structure. Sustainable finance will produce 11.1% energy efficiency. The findings are unaffected by endogeneity and remain solid when considering heterogeneity. The degree of environmental regulation and the implementation of low-carbon pilot policies moderates this process. Sustainable finance has a more significant impact on energy efficiency in non-low-carbon pilot cities with strict environmental regulations. Additionally, due to the variation in technology levels, the effect of sustainable finance on energy efficiency will also experience structural shifts.The improving effect of sustainable finance on energy efficiency increases with the technology level.Through these studies, we aim to offer insightful recommendations for accurately formulating and applying sustainable finance development strategies.